Realist Evaluation of Autism ServiCe Delivery (RE-ASCeD): which diagnostic pathways work best, for whom and in what context? Protocol for a rapid realist review - Patricia Wilson; Ian Male; William Farr; Wenjing Zhang (BMJ Open, 2020)
Introduction The National Health Service (NHS) Long-Term Plan (2019) acknowledges that children and young people with suspected autism wait too long for diagnostic assessment and sets out to reduce waiting times. However, diagnostic pathways vary with limited evidence on what model works best, for whom and in what circumstances. The National Autism Plan for Children (2003) recommended that assessment should be completed within 13 weeks but referral to diagnosis can take as long as 799 days.This Rapid Realist Review (RRR) is the first work package in a national programme of research: a Realist Evaluation of Autism ServiCe Delivery (RE-ASCeD). We explore how particular approaches may deliver high-quality and timely autism diagnostic services for children with possible autism; high quality is defined as compliant with National Institute for Heath and Care Excellence (2011) guidelines, and timely as a pathway lasting no more than one calendar year, based on previous work.Methods and analysis RRR is a well-established approach to synthesising evidence within a compressed timeframe to identify models of service delivery leading to desired outcomes. RRR works backwards from intended outcomes, identified by NICE guidelines and the NHS England Long-Term Plan. The focus is a clearly defined intervention (the diagnostic pathway), associated with specific outcomes (high quality and timely), within a particular set of parameters (Autism and Child & Adolescent Mental Health services in the UK). Our Expert Stakeholder Group consists of policymakers, content experts and knowledge users with a wide range of experience to supplement, tailor and expedite the process. The RRR is consistent with Realist And Meta-narrative Evidence Syntheses: Evolving Standards (RAMESES) and includes identifying the research question, searching for information, quality appraisal, data extraction, synthesising the evidence, validation of findings with experts and dissemination.Ethics and dissemination Ethical approval not required. Findings will inform the wider RE-ASCeD evaluation and be reported to NHS England.Trial registration number NCT04422483. This protocol relates to Pre-results.